Efficiency and Durability Assessment of Soil Stabilization using Waste Tire Shreds - Artoshi, Idrees Majeed Kareem; Abdulateef, Lana Ayad; Farman, Ibrahim Hasan; Ahmed, Ahmed Mohammed (Engineering, Technology & Applied Science Research, 2024)
Tire waste constitutes an undesirable surplus within urban industrial contexts, presenting a persistent annual increase on a global scale. Consequently, the reduction of tire waste through alternative approaches has attracted the interest of researchers around the world. This study evaluated the efficacy of using tire shreds as soil stabilizers to enhance the strength properties of the mixture in three proportions. Tire shred content of 10, 20, and 30% resulted in reduced CBR values of 3.3, 2.98, and 2.3%, respectively, compared to 4.4% without tire shred content. In addition, the direct shear test revealed that the increase in tire shred content significantly increased shear stress, as 10, 20, and 30% tire shred content resulted in 82.25, 84.14, and 85.87 kPa, respectively. Consequently, tire pieces can be used along with soil as an alternative mixture material in retaining structures.